Clinical Observation of Sling Exercise Therapy and Meridian Plucking Manipulation on Lumbar Disc Herniation - LI Li; Ziyun FENG; Jinglong SUN (康复学报)
Objective:To observe the clinical effect of sling exercise therapy (SET) and meridian plucking manipulation in the treatment of patients with lumbar disc herniation (LDH).Methods:A total of 90 LDH patients were randomly assigned to meridian plucking manipulation group (n=30), SET group (n=30), SET and meridian plucking manipulation group (n=30). Each group received corresponding treatment for five times per week and one week as a course. After four courses of treatment, the therapeutic effect and changes of VAS, JOA, ODI and back extensor muscle strength of 3 groups were observed.Results:The effective rate in SET and meridian plucking manipulation group was higher than that of other two groups (P<0.05). After the treatment, the VAS and ODI index score in three groups were significantly decreased, but the degree of improvement in SET and meridian plucking manipulation group was higher than that of other two groups (P<0.05). The JOA score and back extensor muscle strength in three groups were significantly increased, but the degree of improvement in SET and meridian plucking manipulation group was higher than that of other two groups (P<0.05).Conclusion:The SET and meridian plucking manipulation has good effect on LDH, and its effect is better than that of SET, meridian plucking manipulation respectively. The method is worth popularizing.